Author Correction: Genetic landscape of 6089 inherited retinal dystrophies affected cases in Spain and their therapeutic and extended epidemiological implications - Irene Perea-Romero (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.